Training manual on vegetable seed systems. Module 1: Integrated vegetable seed systems. Integrated vegetable seed systems development in ethnic minority communities in Northern Vietnam for enhanced nutrition and income security - Swaans, Kees; Trinh, Quang Tuan; Nabuuma, Deborah; Stomph, Tjeerd-Jan (2024)
Vegetables are a main source of income and nutrition for ethnic minority farmers in Vietnam’s Northern highlands. While value chains for fresh produce and seed markets offer significant opportunities for development—particularly for women and youth—the current smallholder seed systems suffer from multiple problems. Such problems include inadequate access to quality seeds, lack of guaranteed product quality, poor storage and treatment practices, and limited smallholder participation in seed value chains. This training manual based on the project’s experiences and lessons learned is designed to assist facilitators in designing and customizing their own training sessions on seed system related topics. The manual is made up of four modules. This is Module 1: Integrated Seed System Development, that provides an introduction of formal and informal vegetable seed systems, their differences and complementarities, key activities and actors, the relation between food security, seed security and diversity, and how challenges can be addressed through integrated seed systems.